PERBAIKAN KUALITAS KIMIA TANAH DASAR KOLAM PODSOLIK MERAH KUNING DENGAN PEMBERIAN PUPUK CAMPURAN ORGANIK DAN ANORGANIK - Saberina Hasibuan; Niken Ayu Pamukas; Syafriadiman '; Ranny Sirait (Berkala Perikanan Terubuk, 2013)
The research was conducted from Juni to November 2013 in a Laboratory ofEnvironment Quality Cultivation, Fisheries and Marine Science Faculty of RiauUniversity. The purposed of this research was to knew improving the chemicalquality of podsolic red yellow pond bottom soil by a given pool mixed fertilize oforganic quail manure and inorganic fertilizers (Urea, SP 36 and KCl) with differentproportions. The method used in thisexperiment was Randomized CompleteDesign with 6 degrees of treatment with 3 replication. The treatment used in thisexperiment was (without treatment), P1 proportion of 100% organic fertilizer(75,96 g): 0% inorganic fertilizers (0 g; 0 g; 0 g), P2 proportion of 70% organicfertilizer (53,17 g): 30% inorganic fertilizers (0.25 g; 0.04 g; 0.14 g), P3proportion of 50% organic fertilizer (26,59 g): 50% inorganic fertilizers (4.16 g;g; 0,68 2.26 g, P4 proportion of 30% organic fertilizer (7.98 g): 70% inorganicfertilizers (5,82 g; 0.95 g; 3.16 g), P5 proportion0% organic fertilizer (0 g): 100%inorganic fertilizers (8.25 g; g; 4,52 1.36 g). Result showed that the provision oforganic and inorganic mixed with different dose effect to improve the chemicalquality of soil as pH, organic matter, cation exchange capacity and phosphate andwater quality too. Treatment that can provide the best influence on thecharacteristics of the land base of the pond is the proportion of 50% organicfertilizer:50% inorganic fertilizers.Keywords :fertilizer doses, quail manure fertilizer, soil quality, water quality